2021
DOI: 10.1016/j.isci.2021.102191
|View full text |Cite
|
Sign up to set email alerts
|

Junction and energy band on novel semiconductor-based fuel cells

Abstract: Fuel cells are highly efficient and green power sources. The typical membrane electrode assembly is necessary for common electrochemical devices. Recent research and development in solid oxide fuel cells have opened up many new opportunities based on the semiconductor or its heterostructure materials. Semiconductor-based fuel cells (SBFCs) realize the fuel cell functionality in a much more straightforward way. This work aims to discuss new strategies and scientific principles of SBFCs by reviewing various nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 153 publications
(246 reference statements)
0
42
0
Order By: Relevance
“…For instance, bulk p-n heterojunction, planar p-n junction, and Schottky junction have been taken into account as a major factor that leads to built-in-field for charge separation, which can block the electrons from passing internally through the devices and thus evade short circuit risk [20,21,[46][47][48]. Based on these working principles, various junction-based fuel cells and relative technologies have been emerged by means of interface modulation method and energy band engineering [49]. Though the SOFC technology has been advanced over the last two decades, unleashing potential of SOFCs requires more attention to be paid on the operation of the commonly used YSZ electrolyte material which has limited ionic conductivity at lower temperatures.…”
Section: Materials and Technologiesmentioning
confidence: 99%
“…For instance, bulk p-n heterojunction, planar p-n junction, and Schottky junction have been taken into account as a major factor that leads to built-in-field for charge separation, which can block the electrons from passing internally through the devices and thus evade short circuit risk [20,21,[46][47][48]. Based on these working principles, various junction-based fuel cells and relative technologies have been emerged by means of interface modulation method and energy band engineering [49]. Though the SOFC technology has been advanced over the last two decades, unleashing potential of SOFCs requires more attention to be paid on the operation of the commonly used YSZ electrolyte material which has limited ionic conductivity at lower temperatures.…”
Section: Materials and Technologiesmentioning
confidence: 99%
“…To date, various two- and more-phase composites from materials with different conductivity types have been used for SLFC fabrication. A review of the materials can be found in [ 8 , 45 ]. In particular, ceria–carbonate electrolytes possess H + and O 2− conduction [ 41 , 46 ]; therefore, in Figure 1 d the formation of H 2 O on the cathode side is shown.…”
Section: Classification Of Sofcmentioning
confidence: 99%
“…Recently, semiconductors are selected to serve as novel electrolytes or key components in SOFCs, particularly in a proposed concept of the semiconductor-based fuel cell (SBFC) technology [ 9 , 10 , 11 , 12 , 13 ]. Analogously to the conventional SOFC, the SBFC technology can realize fuel cell function by converting chemical energy into electrical power.…”
Section: Introductionmentioning
confidence: 99%
“…The semiconductor–ionic conductor layer in SBFC has been dominantly investigated based on the dual- or multiphase homogeneous composites [ 15 , 16 , 17 , 18 , 19 ]. For example, the typical ionic conductors Gd 3+ - or Sm 3+ -doped ceria (GDC or SDC) are composited with a semiconducting LiNiZn-based oxide as the core component to realize the fuel cell functions [ 10 ]. In this regard, the ion-conducting and semiconducting phases can provide the percolating passageways for ions’ transfer, including O 2− and H + ions, while the electron conduction is suppressed by the formed junction in the semiconductor phase.…”
Section: Introductionmentioning
confidence: 99%